Collective excitations in unconventional superconductors and superfluids / P N Brusov; Pavel Brusov; World Scientific - Brusov, P. N
This is the first monograph that strives to give a complete and detailed description of the collective modes (CMs) in unconventional superfluids and superconductors (UCSF & SC). Using the most powerful method of modern theoretical physics - the path (functional) integral technique -- authors build the three- and two-dimensional models for s-, p- and d-wave pairing in neutral as well as in charged Fermi-systems, models of superfluid Bose-systems and Fermi-Bose-mixtures. Within these models they study the collective properties of such systems as superfluid 3He, superfluid 4He, superfluid 3He-4He mixtures, superfluid 3He-films, superfluid 3He and superfluid 3He-4He mixtures in aerogel, high temperature superconductors, heavy-fermion superconductors, superconducting films etc. Authors compare their results with experimental data and predict a lot of new experiments on CMs study. This opens for experimentalists new possibilities for search of new intriguing features of collective behavior of UCSF & SC. The monograph creates the new scientific direction - the spectroscopy of collective modes in unconventional superfluids and superconductors. It will be useful for both theorists and experimentalists, studying superfluids and superconductors, low temperature physics, condensed matter physics, solid state physics. It could be used by graduate students specializing in the same areas.